Healthcare Professionals’ Application and Integration of Physical Activity in Routine Practice with Older Adults: A Qualitative Study - Conor Cunningham (MDPI AG, 2021)
Healthcare professionals (HCPs) have a key role in promoting physical activity, particularly among populations at greatest risk of poor health due to physical inactivity. This research explored HCPs’ knowledge, decision making, and routine practice of physical activity promotion with older adults. Furthermore, it aimed to enhance our understanding of the supports that HCPs need to effectively promote physical activity in routine practice across a wide range of healthcare professions, settings, and sectors. Semi-structured online interviews were completed with HCPs between November 2020–March 2021. Data were first analysed by coding instances within the transcripts, mapping onto relevant Theoretical Domains Framework (TDF) domains utilising a deductive thematic analysis approach. The data were then analysed utilising an inductive approach to thematically generate explanatory subthemes within the identified domains. Participants (n = 63) included general practitioners (15.87%), occupational therapists (30.16%), physiotherapists (38.10%), and nurses (15.87%) from the island of Ireland (Ireland and Northern Ireland). Of those interviewed, 10 (15.87%) were male and 53 (84.13%) were female. Two thirds (65.08%) were HCPs practicing in Ireland. Domains and subthemes related to the application of physical activity, and emergent themes on developing practice to support the application and integration of physical activity in routine practice are discussed. HCPs identified that focused education, appropriate training, and access to tailored resources are all essential to support the promotion of physical activity in routine practice. For such supports to be effective, a ‘cultural shift’ is required in HCP training and health service provision to adopt the growing evidence base that physical activity promotion must be part of disease prevention and treatment in routine practice. HCPs highlighted a range of areas for service development to support them to promote physical activity. Further research is required to explore the feasibility of implementing these recommendations in routine practice.